A bottom-up view of the Johannesburg Inclusionary Housing Policy: exploring the people's perspective - Mahlalela, Simangele (My University, 2021)
The South African Constitution states that “everyone has the right to have access to adequate housing” and that “the state must take reasonable legislative and other measures, within its available resources, to achieve the progressive realisation of this right”. Thanks in large part to apartheid settlement planning, South African cities are characterised by disintegrated and sprawling settlement patterns. Since the dawn of democracy in 1994, post-apartheid policies have been deeply embedded in redressing past spatial imbalances, and housing has been at the forefront of this. Policies such as the White Paper on Housing (1994), the Reconstruction and Development Programme (1994), the Growth Employment and Redistribution policy (1996), Breaking New Ground (2004) and the National Development Plan (2012) have all been developed with the aim of providing housing for low-income groups. In an effort to address the affordable housing backlog, these subsidised houses have been provided on the peripheral city areas and this has in turn further segregated low-income groups. As with all South African cities, this is the case with Johannesburg and in an effort to counteract this, the city developed an Inclusionary Housing Policy to promote the integration and inclusion of low-income households into well-located areas. This research therefore aims to interrogate the feasibility of the City of Johannesburg Inclusionary Housing Policy through the exploration of low-income households’ housing attributes, preferences and behavior in making housing decisions. Alexandra was selected as the study area for this research because not only is the township a low-income area with prominent housing challenges ,it is also located directly adjacent to affluent Sandton. The researcher made use of a qualitative research approach and conducted interviews using interview guides with 65 participants. The interview guides were informed by the asset-vulnerability framework which expresses a view on how households manage their assets - tangible and intangible -in order to maximise their livelihoods. The research data was analysed using thematic content analysis, which allowed the researcher to classify and present the findings thematically. The research findings indicate that low-income households in Alexandra earning between R3,501 to R7,000 cannot afford inclusionary rental units of R2,100 as they pay much less for backyard rooms in Alexandra and do not pay for some services and utilities there. Most of these households are currently satisfied with their living conditions due to the proximal amenities, job opportunities in and around Alex as well as social relations and social networks that they have established with neighbours. The findings from this research can assist in guiding policy formulation on affordable housing and evaluating the impact of these types of government initiatives on low-income households
A research report submitted to the Faculty of Engineering and Built Environment, University of Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the Degree of MSc Building (Property Development and Management), 2021